2021
DOI: 10.1080/13102818.2021.1892525
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community changes during the mechanized production of light aromaXiaoqu baijiu

Abstract: Multi-microorganisms mixed fermentation is the main characteristic of Chinese baijiu brewing. In this study, plate culture and high-throughput sequencing were used to investigate the changes in microbial community during baijiu brewing. The results revealed that fungi accounted for the largest number of culturable microorganisms, followed by bacteria and molds. The diversity of bacteria and fungi first increased and then decreased, before increasing slightly at the late stage. Most microbial species came from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Wang and Xu ( 2019 ), and Huang et al ( 2020 ) revealed Bacillus and yeast were the most influential microorganisms in the early stage of fermentation, and lactic acid bacteria predominated in the late fermentation phase of light-flavor Baijiu . Hu et al ( 2021b ) used HTS to investigate the structure of the microbial community and indicated that the core microbes were Lactobacillus , A. pasteurianus , S. cerevisia e, W. anomalus , Aspergillus , and R. oryzae at the end of fermentation in the mechanized light-flavor Xiaoqu Baijiu production, which were basically in line with our results. But we newly found a fungus Condenascus that has not been reported in Baijiu , which formerly belonged to the classification of Thielavia (Wang et al 2019a ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Wang and Xu ( 2019 ), and Huang et al ( 2020 ) revealed Bacillus and yeast were the most influential microorganisms in the early stage of fermentation, and lactic acid bacteria predominated in the late fermentation phase of light-flavor Baijiu . Hu et al ( 2021b ) used HTS to investigate the structure of the microbial community and indicated that the core microbes were Lactobacillus , A. pasteurianus , S. cerevisia e, W. anomalus , Aspergillus , and R. oryzae at the end of fermentation in the mechanized light-flavor Xiaoqu Baijiu production, which were basically in line with our results. But we newly found a fungus Condenascus that has not been reported in Baijiu , which formerly belonged to the classification of Thielavia (Wang et al 2019a ).…”
Section: Discussionsupporting
confidence: 89%
“…According to the production process, Jiuqu includes Daqu (Made with raw wheat, barley and/or peas), Xiaoqu (Made with rice or rice bran), and Fuqu (Made with bran) (Jin et al 2017 ). Light-flavor Xiaoqu Baijiu is produced by solid-state fermentation of sorghum with Xiaoqu (starter) containing various microbes and their complex interactions, which is a representative product made by Jing Brand Co., Ltd., one of the largest and most influential manufacturers of Xiaoqu Baijiu based on mechanized technology in China (Hu et al 2021b ). The quality evaluation standard of light-flavor Xiaoqu Baijiu mainly depends on sensory indexes and varieties and contents of core flavor compounds, which are associated with microbial metabolism during brewing process.…”
Section: Introductionmentioning
confidence: 99%
“…Chinese Baijiu can be divided into 12 types according to their flavors. Among them, Maotai flavor, Luzhou flavor, light flavor, and rice flavor are the basic four flavor types, and other baijiu is the extension of these four flavors ( Zheng and Han, 2016 ; Xu et al, 2017b ; Hu Y. et al, 2021 ). The relationship between the 12 flavored baijiu types is shown in Figure 1 .…”
Section: Flavor Types and Fermentation Microorganisms Of Chinese Baijiumentioning
confidence: 99%
“…According to the practical production experiences, the TQ with red heart is often considered to be a reflection of high quality. In previous studies, a few yeasts, molds, and bacteria ( Hu et al, 2021a , b ; Tang et al, 2022 ), including Monascus were isolated from LATB. Then, Zhu et al (2014) reported that three Monascus ruber were isolated from red-heart Langjiu Daqu by plate separation.…”
Section: Introductionmentioning
confidence: 99%